Single-Cell Transcriptomics Reveals Peripheral Immune Responses in Anti-Synthetase Syndrome-Associated Interstitial Lung Disease - Zhu, Lili; Cao, Zhong; Wang, Shiyao; Zhang, Changshui; Fang, Lei; Ren, Yanhong; Xie, Bingbing; Geng, Jing; Xie, Sheng; Zhao, Ling; Ma, Li; Dai, Huaping; et al. (Frontiers in Immunology, 2022)
Objective Interstitial lung diseases (ILDs) secondary to anti-synthetase syndrome (ASS) greatly influence the prognoses of patients with ASS. Here we aimed to investigate the peripheral immune responses to understand the pathogenesis of this condition. Methods We performed single-cell RNA sequencing (scRNA-seq) of peripheral blood mononuclear cells (PBMCs) from 5 patients with ASS-ILD and 3 healthy donors (HDs). Flow cytometry of PBMCs was performed to replenish the results of scRNA-seq. Results We used scRNA-seq to depict a high-resolution visualization of cellular landscape in PBMCs from patients with ASS-ILD. Patients showed upregulated interferon responses among NK cells, monocytes, T cells, and B cells. And the ratio of effector memory CD8 T cells to naïve CD8 T cells was significantly higher in patients than that in HDs. Additionally, Th1, Th2, and Th17 cell differentiation signaling pathways were enriched in T cells. Flow cytometry analyses showed increased proportions of Th17 cells and Th2 cells, and decreased proportion of Th1 cells in patients with ASS-ILD when compared with HDs, evaluated by the expression patterns of chemokine receptors. Conclusions The scRNA-seq data analyses reveal that ASS-ILD is characterized by upregulated interferon responses, altered CD8 T cell homeostasis, and involvement of differentiation signaling pathways of CD4 T cells. The flow cytometry analyses show that the proportions of Th17 cells and Th2 cells are increased and the proportion of Th1 cells is decreased in patients with ASS-ILD. These findings may provide foundations of novel therapeutic targets for patients with this condition.